PANCASILA DAN SUMPAH “PALAPA” GADJAH MADA - Djaja Hendra (Jurnal Ilmiah Mimbar Demokrasi, 2019)
The presence of Pancasila nowadays and in the future or the spirit of “Palapa” oath in the past, is functioned as the attaching base and the unity – device for Indonesian nation and its archipelago. We realize truly that this nation consists of various tribes, religions, languages, ethnics, groups, ecology, etc; it needs to be kept, to be preserved, to be conserved. If it is ignored, it can ‘explode’ in anytime so that it needs in depth thinking and strategies to handle and to finish it. That thing has to be done so that it will not make any difficulty in the next day, so it has to be on a passion, maintained and fought for about the Pancasila and the spirit of “Palapa” oath. As the attachment device of the nation, both Pancasila and Palapa oath are taken from the root of the culture of the nation itself: so that it become familiar, close and usual for us as a nation. Though, both of them present according to the situation of the era, they are believed be able to be the ideology of a country, Indonesia nation. Keyword: Pancasila, Oath, explode, unity-device, ideology